(untitled) (Fiep Bulletin - online, 2014)
Sexuality is integrant part of the Health, quality of life and general well-being of the human being. Two of the physical 0 variable of paper more of the one than basic in the sexual performance of the woman, are exactly the force and the motor coordination of the muscles of the pelvic wooden floor. The objectives of this work had been to correlate the quality of sexual life of women with the muscular function of the pelvic wooden floor and to verify where stage of the sexual act the found sexual dysfunction. Study of transversal cut, carried through with 55 women, it consisted of the collection of data for the instrument Questionnaire of Feminine Sexual Dysfunction and the evaluation of the muscular function of AP for the bidigital touch. The joined results had been: 37% of the women are said satisfied, very satisfied 27% with its global sexual life, and only 5% are very unsatisfied and 31% are little satisfied. When evaluated how much the muscular function of AP, 47% of the participants they had presented degree 2, 29% degree 3, 20% degree 1, only 4% degree 0 of muscular function. The very satisfied women, 40% had presented degree 3, 46.6% degree 2, and 6.7% degree 1 and 0. The ones that had answered satisfied, 40% had presented degree 3, 30% degree 2, 25% degree 1, 5% degree 0. The little satisfied women with regard to sexual life, 11.8% had presented degree 3, 64.7% degree 2, 23.5% degree 1, none presented degree 0. Of that they had answered to be very unsatisfied, 66.6% had presented degree 2 and 33.3% degree 1. With the gotten data of this study it could be concluded that it had directly proportional relation of the level of satisfaction of the sexual life with the muscular function of AP, was possible to observe that how much better the muscular function, better the satisfaction in the sexual life. The more frequent sexual dysfunction had been disturbance of the desire in 58,2%, disturbance of the excitement in 55,6%, disturbance of orgasm with coitus in 83,0%, without coitus in 57,4%.